Book Reviews - Lise Kanckos; Mikko Sillfors (Approaching Religion, 2012)
Believing in Belonging: Belief & Social Identity in the Modern World by Abby Day is reviewed by Lise Kanckos.Religion and the New Atheism: A Critical Appraisal, edited by Amarnath Amarasingam, is reviewed by Mikko Sillfors.